Assessment on the awareness level about diarrhoea and its management among mothers attending outpatient department in a rural hospital of West Bengal, India - Basu, Pampa; Chakrabartty, Arupkumar; Bhattacharya, Salil; Bhattacharya, Krishnadas; Dasgupta, Urmila; Bhattacharya, Saikat; Ali, Kazi Monjur (Bangladesh Journal of Medical Science, 2019)
Background: Diarrhoea is one of the leading causes of under-five childhood morbidity and mortality in India, despite the availability of easy interventions through oral rehydration at the community level. The level of knowledge varies from country to country and within the country, further variations exist in state, district and sub district level based on difference in socio-demographic characteristics of the population. And based on these variations, different community needs different health education efforts in its extent and approaches. It was therefore relevant to explore the level of awareness about diarrhoea and its management among the mothers who were the first level of caregivers. Objective: To assess the level of knowledge about diarrhoea and oral rehydration therapy among the mothers having their children of 6 months to 5 yrs with diarrhea Materials and methods: It was a facility based cross-sectional descriptive epidemiological study conducted among 62 mothers having their children of 6 months to five years with diarrhoea. Mothers attended a rural hospital under the geographical area of Madhyamgram in North 24 Parganas district of West Bengal, India. Data was collected by face to face interview of the mothers in the outpatient department of the hospital using a pre-designed and pre-tested questionnaire. The analysis was done in Statistical Package for Social Sciences (SPSS), version 20.0 using bivariate and multivariate (multiple logistic regression model) to examine the statistical significance at 95% confidence interval. Results: Mean knowledge score was 7.8 (Range 0-17). Lower knowledge score group (0-8) accounted to 36 persons (37.1%) and higher knowledge group (9-19) accounted to 26 persons (62.9%). Knowledge about alarming symptoms of the dehydration was significantly poor. At the individual level, literacy of women and their caste were strongly associated with the knowledge about diarrhoea and its management. At the household level, the way of the disposal of household garbage was also strongly associated. Conclusion: Considering the poor knowledge of the mothers, the study recommends for extensive health education measures widely in the community with a special focus for the illiterate and socio-economically lower groups, and also for the families having the practice of open garbage disposal. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.267-273